2021
DOI: 10.1017/s0022278x20000713
|View full text |Cite
|
Sign up to set email alerts
|

Recite the last bylaw: chiefs and child marriage reform in Malawi

Abstract: In the study of modern chieftaincy in Africa, scholars have identified chiefs as important intermediaries for promoting increased voter turnout, new health policies and development initiatives. I add to this literature the importance of chiefs as cultural intermediaries. Using recent child marriage reform efforts in Malawi as a case study, I find that chiefs are key actors needed to implement culturally embedded policy changes. Drawing on descriptive evidence from 12 months of fieldwork across all three region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…12 13 Another study in Malawi highlighted the promise of chiefs as cultural intermediaries in child marriage reform, implementing culturally embedded policy change by mobilising democratic and non-democratic powers. 14 …”
Section: Resultsmentioning
confidence: 99%
“…12 13 Another study in Malawi highlighted the promise of chiefs as cultural intermediaries in child marriage reform, implementing culturally embedded policy change by mobilising democratic and non-democratic powers. 14 …”
Section: Resultsmentioning
confidence: 99%
“…Chimbwinda payments reveal how the power to regulate girls' sexuality is vested in and maintained by chiefs in contemporary settings. These are not the only payments that chiefs receive, but they are critically important in sustaining the institutions of traditional authority [5]. In controlling the ritual processes around marriages and sexuality, chiefs exert control over families, communities, and unmarried girlsdespecially over those who are uninitiated or pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them viewed the sharing as an act of selflessness. In a recent study conducted in Malawi on the role of chiefs in ending child marriages, it was found that some chiefs used their proceeds collected as fines to pay for teacher salaries and other things [5]. However, in the narratives above, beyond the aspect of transparency and generosity that chiefs invoke in sharing the proceeds is the creation and perpetuation of a social norm.…”
Section: Chiefship and The Regulation Of Girls' Sexualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ways in which such interventions shape the roles of selected community leaders and create male gatekeepers constraining women’s emancipation goes unchecked. There is conflicting evidence about persistent social, economic, and political factors and the return of practices such as child marriage, which indicates that interventions may have to be more context-specific (Maiden 2021; Affoum & Recavarrenn 2020). Recent studies show that perceptions of early marriage are often at odds with the abstract concepts adopted in policy circles.…”
Section: Discussionmentioning
confidence: 99%